Pengaruh Rasio Likuiditas dan Rasio Aktivitas Terhadap Harga Saham Pada Perusahaan Sektor Healthcare yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2022-2024: Penelitian - Lainatusshifa Kemal (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the effect of liquidity ratio and activity ratio on stock prices of healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research employs a quantitative approach with an explanatory method, using secondary data obtained from the companies’ financial statements. The sample consists of 27 companies selected through purposive sampling. Data analysis includes descriptive statistics, classical assumption tests, multiple linear regression, and both partial (t-test) and simultaneous (F-test) hypothesis testing. The results indicate that the liquidity ratio (Current Ratio) has a positive but statistically insignificant effect on stock prices, while the activity ratio (Total Asset Turnover) has a positive and significant effect. Simultaneously, both ratios have a significant effect on stock prices with a coefficient of determination (R²) of 0.62, meaning that 62% of the variation in stock prices can be explained by the two variables. These findings suggest that asset utilization efficiency is a more dominant factor considered by investors compared to the company’s liquidity level.